Fragment księgozbioru Ponińskich z Kościelca w zbiorach Wojewódzkiej i Miejskiej Biblioteki Publicznej w Bydgoszczy - Ryszard Nowicki (Biblioteka)
This article attempts at reconstructing the history of a private book collection that belonged to the Poniński family from Greater Poland settled in Kościelec Kujawski, a small village near Inowrocław. However, the collection’s profile, size and its final shape can only be determined hypothetically since there are too many gaps to establish something with certainty. During the war the book collection was dispersed and only a small fraction, now held at the public library in Bydgoszcz, survived. Those items from the collection that have been identified are described in detail. A further search for the books fromthe dispersed collection could cast more light on this valuable manorial library that so far has been virtually non-existent in all Polish bibliographies and monographs.